Evaluation of zoobenthic assemblages and recovery following petroleum spill in a coastal area of Río de la Plata estuarine system, South America - Ocon, Carolina Silvia (2008)
The objective of this work was to analyse zoobenthic assemblages in the coastal sector of the Río de La Plata, Argentina, after a petroleum spill. Sampling stations were located in representative sites of various landscapes. Structure, composition, physico-chemical parameters and seasonal changes were recorded in order to assess taxocenosis evolution during the period 1999–2003. Recovery signs were estimated by means of biotic indices and the presence of sensitive species. Tolerant species were dominant in heavily polluted sites, with low diversity and water quality values, according to the biotic indices used. In certain zones, sediment quality remains impoverished, with a visible oil film on the surface. However, during the last sampling, some points showed an increase in biotic indices, pointing to a slight improvement in environmental conditions.